MENGATUR DESA WISATA: PERAN TOKOH MASYARAKAT MEMBANGUN INISIATIF KOLEKTIF DALAM PENGEMBANGAN PARIWISATA BERBASIS KOMUNITAS - Gangsar Hanajayani; Sariffuddin Sariffuddin (TATALOKA, 2018)
The phenomenon of the continuous development of rural tourism in Indonesia is not balanced by skill capacity and professional knowledge on the managers. By self-taught and learning by doing they proceed to realize the rural tourism to capitalize local resources in order to improve their welfare. Community leaders as key figures in village development have an important role in mobilizing people to marketing (the village). The importance of community leaders is the goal of this article, focusing on the role of community leaders in the management of community-based tourism. The case study was taken from the management of Kaligono Tourism Village in Purworejo Regency which is one of the best national rural tourisms according to the Ministry of Tourism and Creative Economy in 2014. Using qualitative methods by selecting interviewees as the informants through snowballing, this article provides information on the role of community leaders in managing the rural tourism, learning and building collective initiatives for rural tourism management. Despite the the low skill and professional knowledge, the community is able to manage the rural tourism by relying on the power of social cohesion to create collective initiatives.